2007
DOI: 10.1097/mnh.0b013e3280dd8c35
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and prognostic significance of acute kidney injury

Abstract: Purpose of review-Acute kidney injury is an increasingly common and potentially catastrophic complication in hospitalized patients. This review summarizes the major epidemiologic studies that have informed our understanding of the incidence and prognostic significance of acute kidney injury.Recent findings-Early observational studies from the 1980s and 1990s established the general epidemiologic features of acute kidney injury, including the incidence, prognostic significance and predisposing medical and surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 74 publications
0
62
1
Order By: Relevance
“…Numerous studies have demonstrated that respiratory failure requiring mechanical ventilation is a key risk factor for mortality in patients with AKI. 6,11,[26][27][28] Of the four studies that have specifically compared outcomes in AKI versus ESRD, [22][23][24][25] only two 24,25 found statistically meaningful factors that were associated with increased mortality in patients with AKI. Remarkably, both reports found that the need for mechanical ventilation was higher in patients with AKI, and that the need for mechanical ventilation was an independent risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that respiratory failure requiring mechanical ventilation is a key risk factor for mortality in patients with AKI. 6,11,[26][27][28] Of the four studies that have specifically compared outcomes in AKI versus ESRD, [22][23][24][25] only two 24,25 found statistically meaningful factors that were associated with increased mortality in patients with AKI. Remarkably, both reports found that the need for mechanical ventilation was higher in patients with AKI, and that the need for mechanical ventilation was an independent risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a slight kidney injury or the presence of fewer associated complications may cause ARF in patients with underlying CKD. [26] In a population-based surveillance study of ARF, 63% of all patients with ARF who required dialysis one year following admission had preexisting CKD. [27] Hospital-acquired acute renal failure (HA-ARF) is considered an iatrogenic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Acute kidney injury is increasingly well recognised as a public health issue and is both a consequence and a predictor of CKD. [10][11][12] Its prevalence (4.9% among hospitalised patients in the USA) is increasing, 13 owing to an ageing population and the growing burden of the same risk factors contributing to the rise in CKD (including obesity, diabetes and hypertension), and also to better recognition.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%